Obstacles to Transforming Centrally-Planned Economies : The Role of Capital Markets - Calvo, Guillermo (IMF Working Papers; Working Paper ;, 1991)
This paper identifies obstacles hindering the transformation of centrally-planned economies (CPEs) into well-functioning market economies. The obstacles identified relate to (i) anticipatory dynamics, (ii) monetary overhang and the budget, and (iii) underdeveloped credit markets. It is demonstrated that these obstacles inhibit the effectiveness of price reform, monetary and credit policies, and trade liberalization. The analysis focuses on various ways to remove the obstacles. In this regard, a special examination is made of the implications of 'cleaning' the balance sheets of enterprises and banks from nonperforming loans, as well as ways to enhance credibility. The paper concludes with a brief discussion of sequencing, 'safety nets,' and their associated obstacles.